2010
DOI: 10.1007/s12192-009-0140-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the shsp genes in Drosophila buzzatii and association between the frequency of Valine mutations in hsp23 and climatic variables along a longitudinal gradient in Australia

Abstract: The small heat shock gene (shsp) cluster of Drosophila buzzatii was sequenced and the gene order and DNA sequence were compared with those of the shsps in Drosophila melanogaster. The D. buzzatii shsp cluster contains an inversion and a duplication of hsp26. A phylogenetic tree was constructed based on hsp26 genes from several Drosophila species of the Sophophora and Drosophila subgenera. The tree shows first a separation of the Sophophora and the Drosophila subgenera and then the Drosophila subgenus is divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Based on these studies, it is well established that HSP expression is an adaptive physiological mechanism for coping with acute thermal stress. Accordingly, population-level comparisons have discovered clinal variation in Hsp23 alleles across environmental thermal gradients in Drosophila buzzatii in Australia (Frydenberg et al, 2010), as well as clines in allele frequencies of Hsp23 and Hsp26 among D. melanogaster populations in Australia (Frydenberg et al, 2003). In addition, laboratory thermal selection studies have found evolved changes in HSP expression to accompany adaptive shifts in upper thermal limits (Rudolph et al, 2010;Kelly et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these studies, it is well established that HSP expression is an adaptive physiological mechanism for coping with acute thermal stress. Accordingly, population-level comparisons have discovered clinal variation in Hsp23 alleles across environmental thermal gradients in Drosophila buzzatii in Australia (Frydenberg et al, 2010), as well as clines in allele frequencies of Hsp23 and Hsp26 among D. melanogaster populations in Australia (Frydenberg et al, 2003). In addition, laboratory thermal selection studies have found evolved changes in HSP expression to accompany adaptive shifts in upper thermal limits (Rudolph et al, 2010;Kelly et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although the finding of association between HSP22 polymorphisms and some certain traits is of high interest, the detailed mechanisms under the phenomenon are still far from well understood. Inspiringly, accumulating evidences have suggested that genetic polymorphisms in the coding regions could affect proteins activity [42] , [43] , which could perhaps explain why they were associated with some certain traits. For example, the mutation of Valine to Leucine can change the biological activity of the antimicrobial peptide protegrin-1 [42] , the specific mutations in Cosmc from patients with Tn syndrome lead to the loss of its chaperone function [44] , and the nonsynonymous mutation in the coding region of human Hsp70 gene can affect the chaperone function [19] .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 11 SNP sites were found in the exon region of PmPIAS , and they demonstrated significant differences between the R and W in genotype and allele. Accumulating evidence suggested that genetic polymorphisms in the coding regions could affect protein activity or effect of translation ( Gottler et al, 2008 ; Frydenberg et al, 2010 ). The SNPs detected in the present study may provide a potential site for the cold tolerance selection in the future.…”
Section: Discussionmentioning
confidence: 99%